APAKAH JANUARY EFFECT TERJADI DI TAHUN 2019? - Woro Hestiningsih; Khanifah Khanifah; Pancawati Hardiningsih (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
Efficient market hyphotesis is still an interesting debate, because there are still pros and cons among practitioners and academics in finance. One market anomaly that is contrary to the theory of efficient capital markets is the January effect or year-end effect is one of the effects on a calendar that is small capitalized stocks tend to rise in price in January. This study aims to determine the effect of the January effect on abnormal return and trading volume activity on LQ45 companies listed on the Indonesia Stock Exchange. Analysis using one way anova shows that abnormal returns occur in the January effect phenomenon while the January effect does not occur in trading volume.